(untitled) (Bangladesh Journal of Medical Science, 2021)
Testicular microlithiasis is an asymptomatic condition associated with calcification within theseminiferous tubule, natural history of which is not clearly known.Association with varioustesticular malignancies warrant regular follow up in patients with microlithiasis. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.194-196